N-Acetyl cysteine exhibits antimicrobial and anti-virulence activity against Salmonella enterica. - Selwan Hamed; Mohamed Emara; Payman Tohidifar; Christopher V Rao (PLoS ONE)
Salmonella enterica is a common foodborne pathogen that causes intestinal illness varying from mild gastroenteritis to life-threatening systemic infections. The frequency of outbreaks due to multidrug-resistant Salmonella has been increased in the past few years with increasing numbers of annual deaths. Therefore, new strategies to control the spread of antimicrobial resistance are required. In this work, we found that N-acetyl cysteine (NAC) inhibits S. enterica at MIC of 3 mg ml-1 and synergistically activates the bactericidal activities of common antibiotics from three-fold for ampicillin and apramycin up to1000-fold for gentamycin. In addition, NAC inhibits the expression of virulence genes at sub-inhibitory concentrations in a dose-dependent manner. The whole-genome sequencing revealed that continuous exposure of S. enterica to NAC leads to the development of resistance; these resistant strains are attenuated for virulence. These results suggest that NAC may be a promising adjuvant to antibiotics for treating S. enterica in combination with other antibiotics.